The antioxidants resveratrol and N-acetylcysteine enhance anthelmintic activity of praziquantel and artesunate against Schistosoma mansoni - Gouveia, M (2019)
Background: Treatment of schistosomiasis has relied on the anthelmintic drug praziquantel (PZQ) for more than a generation. Despite its celebrated performance for treatment and control of schistosomiasis and other platyhelminth infections, praziquantel has some shortcomings and the inability of this drug to counteract disease sequelae prompts the need for novel therapeutic strategies. Methods: Using a host-parasite model involving Biomphalaria glabrata and Schistosoma mansoni we established mechanical transformation of S. mansoni cercariae into newly transformed schistosomula (NTS) and characterized optimal culture conditions. Thereafter, we investigated the antischistosomal activity and ability of the antioxidants N-acetylcysteine (NAC) and resveratrol (RESV) to augment the performance of praziquantel and/or artesunate (AS) against larval stages of the parasite. Drug effects were evaluated by using an automated microscopical system to study live and fixed parasites and by transmission electron microscopy (TEM). Results: Transformation rates of cercariae to schistosomula reached ~ 70% when the manipulation process was optimized. Several culture media were tested, with M199 supplemented with HEPES found to be suitable for S. mansoni NTS. Among the antioxidants studied, RESV alone or combined with anthelminthic drugs achieved better results rather N-acetylcysteine (NAC). TEM observations demonstrated that the combination of AS + RESV induced severe, extensive alterations to the tegument and subtegument of NTS when compared to the constituent compounds alone. Two anthelmintic-antioxidant combinations, praziquantel-resveratrol [combination index (CI) = 0.74] and artesunate-resveratrol (CI = 0.34) displayed moderate and strong synergy, respectively. Conclusions: The use of viability markers including staining with propidium iodide increased the accuracy of drug screening assays against S. mansoni NTS. The synergies observed might be the consequence of increased action by RESV on targets of AS and PZQ and/or they may act through concomitantly on discrete targets to enhance overall antischistosomal action. Combinations of active agents, preferably with discrete modes of action including activity against developmental stages and/or the potential to ameliorate infection-associated pathology, might be pursued in order to identify novel therapeutic interventions.